Acute Myocardial Infarction in Women, a Study on Risk Factors, Angiographic Features and Outcomes - Chapagain Koirala, Prabha; Sah, Ram Kishor; Sherpa, Kunjang; Poudyal, Samir; Gautam, Binayak; Koirala, Richa (Journal of Nepal Health Research Council, 2024)
Background: Women with acute coronary syndrome are more likely to have cardiovascular disease risk factors and atypical symptoms as compared to men. In Nepal, there is a rising trend of Coronary Artery Disease and myocardial infarction in women. However, research on acute myocardial infarction in women is lacking. The aim of this study was to study the cardiac risk factors, clinical features, angiographic features, and outcome of acute myocardial infarction in Nepalese women admitted to Hospital. Methods: This was a cross sectional study done at Shahid Gangalal National Heart Center Kathmandu from September 2016 to March 2017. Female patients admitted with a diagnosis of acute ST-segment elevation myocardial infarction or non–ST segment elevation myocardial infarction, who fulfilled the inclusion criteria were included in the study. The details of the patients, demographic profile, major clinical symptoms, major coronary artery disease risk factors, angiographic features and outcomes were recorded and assessed during the study period. Coronary angiography was done in 112 patients out of 178 patients.Results: Out of 178 patients, 85.95 % had ST-segment elevation myocardial infarction and 14.05% had non–ST segment elevation myocardial infarction. The mean patient age was 62.53 ± 12.1. 26.4% patients were of age less than 55 years. Major risk factors were central obesity (94.61%), dyslipidemia due to low HDL (78.65%). hypertension (54.49%), smoking (54.49%) and type 2 diabetes (34.83%). The most common atypical symptoms were shortness of breath (35.39 %,) , nausea and vomiting (23. 6%) and epigastric pain (6.74%), Single vessel disease was found in 36%; double vessel disease in 26.3% and triple vessel disease in 28.9% of patients. The primary outcome of in- hospital mortality was 3.37 %. Conclusions: Our study showed that significant number of females had Coronary Artery Disease at early age. Among women with myocardial infarction in Nepal, obesity due to high waist to hip ratio was the most common risk factor followed by dyslipidemia due to low high density lipoproteins, smoking, hypertension, and diabetes. Atypical symptoms were also common findings. Single vessel disease was the most common lesion and left anterior descending artery was the most commonly involved vessel. Mortality was seen in ST-segment elevation myocardial infarction patients only.Keywords: MI in women; outcome; risk factors.